2022
DOI: 10.25122/jml-2021-0425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of roselle leaf (Hibiscus sabdariffa L.) extract gel on wound healing

Abstract: Roselle (Hibiscus sabdariffa L.) belongs to the genus Hibiscus with proven anti-inflammatory, antioxidant, and antimicrobial properties. Scientific evidence associated roselle content with bioactive compounds, such as phenolic acids, flavonoids, and anthocyanin. Most studies focused on their petals, while research on leaf extract on wound healing has never been done. This study aimed to assess the effect of roselle leaf extract on wound healing in rats. This was an experimental laboratory study with a posttest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Monocyte cells express TNFα in their cytoplasm and surrounding their brownish membrane. 13 Based on the results of the ANOVA different test (table 2 and figure 1), it was found that TNF Alpha was not significantly different, with a p-value of 0.054. This could be because the tissue staining failed, leading to false positive results, or because different colors were used to prepare the histological images.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Monocyte cells express TNFα in their cytoplasm and surrounding their brownish membrane. 13 Based on the results of the ANOVA different test (table 2 and figure 1), it was found that TNF Alpha was not significantly different, with a p-value of 0.054. This could be because the tissue staining failed, leading to false positive results, or because different colors were used to prepare the histological images.…”
Section: Discussionmentioning
confidence: 95%
“…Rosella flower extract 15% 13 in paste preparation made by preparing dried roselle flower obtained from Temon District, Kulon Progo Regency, Yogyakarta, as much as 500 grams. The process of drying roselle flower using an oven at 40ºC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently reported flavonoids that are found abundantly are quercetin-3-glucoside, methyl epigallocatechin, myricetin, quercetin, rutin, and kaempferol [ 26 ]. Other types of flavonoids present in roselle include sabdaritrin, hibiscitrin, gossytrin, gossypitrin, luteolin, and pelargonidic acid [ 27 , 28 ]. In some studies, phenolic acid was noted to be present in roselle calyx, stems, and leaves.…”
Section: Origin and Beneficial Use Of Rosellementioning
confidence: 99%